Use of hemostatic powder in treatment of upper gastrointestinal bleeding: a systematic review and meta-analysis - de Rezende, Daniel Tavares; Brunaldi, Vitor Ottoboni; Bernardo, Wanderley Marques; Ribeiro, Igor Braga; Mota, Raquel Cristina Lins; Baracat, Felipe Iankelevich; de Moura, Diogo Turiani Hourneaux; Baracat, Renato; Matuguma, Sergio Eiji; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2019)
Background and study aims TC-325 is a novel mineral hemostatic powder that creates a mechanical barrier by absorbing blood components and promoting clotting. Recently approved for use in humans, it has shown promise for treatment of upper gastrointestinal bleeding (UGIB). However, because there have been no large studies of TC-325, its true efficacy and safety profile remain unknown. We performed a systematic review and meta-analysis to determine the safety and efficacy of TC-325 in treating UGIB, based on rates of initial hemostasis, rebleeding, and adverse events (AEs). Methods We searched the MEDLINE/PubMed, EMBASE, CENTRAL, Latin-American and Caribbean Health Sciences Literature databases, as well as the gray literature, to identify articles describing use of TC-325 up to October 2018. Primary outcomes were initial hemostasis and rebleeding. AEs were described as a secondary outcome. Risk of bias was assessed with international scores.Results We identified 2077 records after removal of duplicates. We included 50 studies, involving a collective total of 1445 patients, in the quantitative synthesis. Primary hemostasis and rebleeding rates were 90.7 % and 26.1 %, respectively. Subgroup analyses showed similar results. Only eight AEs were reported.Conclusions TC-325 appears to be a safe, effective treatment for UGIB. The overall rate of initial hemostasis after TC-325 use is high, regardless of etiology of bleeding or whether TC-325 is used as a primary or rescue therapy. Although it is also associated with high rebleeding rates, rates of AEs and equipment failure after TC-325 use are extremely low.